On the Benefits of Being Sexually Autonomous and Costs of Being Sexually Pressured: The Contributions of Different Motives for Sex to Experiences of Sexual Well-Being - Gravel, Emilie (Université d'Ottawa / University of Ottawa, 2017)
A growing number of studies suggest that the reasons for which people engage in sexual activities matter for their sexual well-being. Grounded in self-determination theory (SDT), this thesis research investigated the contributions of autonomous and controlled sexual motivation to sexual well-being. These objectives were achieved through a series of five studies presented in four manuscripts. In Manuscript 1, we validated the Sexual Motivation Scale (SexMS), a measure of self-regulation for sexual activities grounded in SDT (Study 1: N = 1,070, Study 2: N = 575). Collectively, the findings provided strong support for the factorial validity of the SexMS. Additionally, the SexMS captured important individual differences in sexual well-being, specifically with respect to sexual satisfaction, sexual distress, and sexual function. Manuscript 2 explored how autonomous and controlled sexual motivation are integrated with broader psychological functioning by examining their motivational antecedents and well-being consequences (N = 828). The results showed that global and relational motivation explained individual differences in autonomous and controlled sexual motivation. Additionally, autonomous and controlled sexual motivation explained individual differences in sexual, relational, and global well-being. Finally, the results suggested that, for the most part, the associations between the motivational antecedents and the well-being consequences of autonomous and controlled sexual motivation followed a heterarchical structure. Next, in Manuscript 3, the motivational sequence proposed by SDT – in which basic psychological needs satisfaction predicts quality of motivation, and in turn quality of psychological functioning – was validated in the context of within-person variations in sexual well-being (N = 113). The results indicated that on days when people experience more basic psychological needs satisfaction during interactions with their partner, their sexual motivation was more autonomous and this was associated with higher sexual well-being. However, basic needs satisfaction did not significantly predict controlled sexual motivation. Additionally, on days when people reported higher controlled sexual motivation, they experienced lower sexual well-being. Finally, in Manuscript 4, we examined the motivational sequence proposed by SDT from a dyadic perspective to better understand the contribution of sexual motivation to sexual well-being in couples (N = 225 couples). Specifically, we examined whether basic needs satisfaction during sexual activities and autonomous and controlled sexual motivation in one partner influenced the sexual well-being of the other partner. The unique contribution of each basic psychological need (i.e., autonomy, competence, and relatedness) to sexual well-being was also investigated. Taken together, the results supported SDT’s predictions regarding the relevance of the motivational sequence and the unique contribution of each basic psychological need in explaining between-couple differences in sexual well-being. However, different patterns of association emerged for women and men, suggesting that in the context of sexual activities within heterosexual relationships, the motivational processes proposed by SDT may be moderated by gender. In sum, the findings from this thesis extend SDT and sexual motivation research. Overall, SDT may provide novel insights on human sexual behaviour, notably by improving our understanding of the factors that can enhance or impede sexual well-being in committed relationships.
Keywords: Sexual motivation; Self-determination theory; Well-being; Sexual health; Basic needs; Motivation; Motives; Relationships